Shared understanding and coordination in team sports. Contribution of viewpoints changes and shared information displays for team situation awareness training - Kermarrec, G.; Cardin, Y.; Bossard, C. (IcSport INSTICC, 2014)
The paper aims at examining the interest of viewpoints changes and shared information displays for promoting shared understanding and decision-making coordination in team sports.The role of technological device such as virtual reality and video-cued training are examined. The paper starts with a description of major features in shared understanding elicited in sport psychology, and then focuses on review and choices concerning the use of virtual reality (VR). Finally, an exploratory study in soccer is presented, supported the idea that, using two properties of VR (viewpoint changing, and displaying player`s judgments), an innovative 2-D video-cued training should enhance shared understanding between four defensive players. First results suggest that such technological device could enhance sharing processes and modify sharedness (i.e. shared knowledge structure) (22)